Circular RNA: Biosynthesis in vitro - Chen, Xinjie; Lu, Yuan (Frontiers in Bioengineering and Biotechnology, 2021)
Circular RNA (circRNA) is a unique type of noncoding RNA molecule. Compared with traditional linear RNA, circRNA is a covalently closed circle produced by a process called backsplicing. CircRNA is abundant in many cells and has rich functions in cells, such as acting as miRNA sponge, protein sponge, protein scaffold, and mRNA regulator. With the continuous development of circRNA study, circRNA has also played an important role in medical applications, including circRNA vaccines and gene therapy. In this review, we illustrate the synthesis of circRNAs in vitro. We focus on biological ligation methods, such as enzymatic ligation from the bacteriophage T4 and ribozyme method. In addition, we summarize the current challenges in the design, synthesis, application, and production of circRNAs, and propose possible solutions in the future. CircRNA is expected to play an essential role in basic research and medical applications.